Dose performance of internal irradiation from incorporated 137CS and 90SR of ichthiofauna of reservoirs located in the territory of the Polessky State Radiation-Ecological Reserve - Gulakov, Andrey V.; Drozdov, Denis N.; Ivantsov, Dmitry N. (Journal of the Belarusian State University. Ecology, 2020)
The paper presents the results of estimating the absorbed dose rate from incorporated 137Cs and 90Sr in the most common species of freshwater ichthyofauna reservoirs of various types located on the territory of the Polessky State Radiation Ecological Reserve. Sampling was carried out during 2019. It was found that the contribution of the water masses of the flowing (river Pripyat), semi-flowing (old channel Nikolaev) and closed (lake Semenitsa) reservoirs to the total annual absorbed dose of internal radiation from 137Cs and 90Sr radionuclides in the mature representatives of the fishing fauna of the PGREZ is insignificant and does not pose a threat for dose effects.